1988
DOI: 10.1192/s0140078900020307
|View full text |Cite
|
Sign up to set email alerts
|

The Local use of Section 136

Abstract: Recent attention has been focused on divergent practices in the implementation of Section 136,' problems in its practice encountered by the police,2 and possible means of improv ing the service and reducing unnecessary detention.3 In these studies, doubts have been raised about the justness of the section, both in principle and in practice, and about the efficiencyand efficacy of its implementation. In the context of the closure of the large psychiatric institutions it seems probable that these issues will bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…3 Where the hospital is used as a place of safety, the hospital managers must ensure that the provisions of section 132 (giving information) are complied with, 3 and so patients should be provided with "Rights leaflet" number 5. 25 It is debatable whether section 136 provides authority to transfer from one place of safety to another, 26 as this is not directly covered in the act. The general opinion of the Royal Society of Health is that transferring from one place of safety to another is legal provided that no assessment has started, 9 but others disagree with this.…”
Section: Discussionmentioning
confidence: 99%
“…3 Where the hospital is used as a place of safety, the hospital managers must ensure that the provisions of section 132 (giving information) are complied with, 3 and so patients should be provided with "Rights leaflet" number 5. 25 It is debatable whether section 136 provides authority to transfer from one place of safety to another, 26 as this is not directly covered in the act. The general opinion of the Royal Society of Health is that transferring from one place of safety to another is legal provided that no assessment has started, 9 but others disagree with this.…”
Section: Discussionmentioning
confidence: 99%
“…If the admission rate truly reflects marked mental disorder then the high admission rate (82%) indicates that detention under Section 136 by the police is appropriate. Weller at al. (1988) studied Section 136 detentions to the now closed Friern Barnet Hospital, whose psychiatric catchment area covered amongst others the Haringey area, and thought that the police tended to diagnose appropriately.…”
Section: Appropriateness Of Police Referralmentioning
confidence: 99%
“…Police views have also been outlined Wallis, 1989), and it has been admitted that they 'bent the rules of Section 136 to cut corners' (Guardian, 1989). However, a brief study of Section 136 admissions to Friern Hospital in North London (Weller et al 1988), showed a significant decrease between 1970 and 1987. Others have shown high rates of schizophrenia, social dysfunction (including lack of a settled abode) and personality disorder (Szmuckler et al 1981).…”
Section: Introductionmentioning
confidence: 98%